Serum Fibroblast Growth Factor-21 Levels Are Associated With Carotid Atherosclerosis Independent of Established Cardiovascular Risk Factors - Chow, Wing Sun; Xu, Aimin; Woo, Yu Cho; Tso, Annette W.K.; Cheung, Stephen C.W.; Fong, Carol H.Y.; Tse, Hung Fat; Chau, Ming Tak; Cheung, Bernard M.Y.; Lam, Karen S.L. (Arteriosclerosis, thrombosis, and vascular biology, 2013)
OBJECTIVE—Serum levels of fibroblast growth factor-21 (FGF21), a metabolic hormone, have been shown to be elevated in subjects with adverse lipid profiles, obesity, metabolic syndrome, impaired glucose tolerance, type 2 diabetes mellitus, and hypertension. Recently, elevated serum FGF21 levels have also been reported in subjects with coronary heart disease or carotid artery plaques. However, whether serum FGF21 is independently associated with atherosclerotic diseases remains unclear. In this study, we examined the relationship between serum FGF21 levels and carotid intima-media thickness (IMT) in a large cohort of Southern Chinese subjects. APPROACH AND RESULTS—The cohort consisted of 670 subjects who underwent carotid IMT measurement. Serum FGF21 levels were measured with an ELISA kit. Serum FGF21 levels positively correlated with carotid IMT in women (r=0.32; P<0.001), but not in men (r=0.06; P=0.305). On multiple linear regression analysis, elevated serum FGF21 level in women was an independent risk factor for increased carotid IMT (P=0.039), together with age (P<0.001) and hypertension (P=0.011), in a model comprising also waist circumference, smoking history, serum creatinine, high sensitive C-reactive protein, dysglycemia, and dyslipidemia (adjusted R=35.8%; P<0.001). Elevated serum FGF21 levels were also a significant independent risk factor of carotid IMT on multiple stepwise regression analysis (P=0.01). CONCLUSIONS—The present study is the first demonstration that elevated serum FGF21 levels are associated with carotid atherosclerosis in humans, independent of established risk factors including adverse lipid profiles and C-reactive protein. The role of FGF21 as a biomarker or therapeutic target of atherosclerotic diseases warrants further investigation.